2019
DOI: 10.1002/jum.15154
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Fatty Liver Indicator: A Simple Tool for Differentiating Steatosis From Nonalcoholic Steatohepatitis: Validity in the Average Obese Population

Abstract: Objectives Steatosis, nonalcoholic steatohepatitis (NASH), and fibrosis/cirrhosis represent a spectrum of fatty liver disease. The ultrasound fatty liver indicator (US‐FLI) evaluates ultrasound (US) features to identify stages of fatty liver disease. We hypothesized that US features could be independent predictors of NASH and that the US‐FLI differentiates steatosis from NASH in the average obese population. Methods A retrospective analysis of 208 patients with normal (n = 14), steatotic (n = 89), and NASH (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Ballestri S et al showed ultrasonographic fatty liver indicator (US-FLI) can accurately identify the severity of histology and is also correlated with WC, BMI, and IR with various steatogenic liver diseases [34]. In addition, Nelson SM et al demonstrated that US-FLI may differentiate steatosis from NASH in the average obese population [35]. Praveenraj et al reported that BMI, WC and WHR had the best predictive ability for NAFLD in a cohort of morbidly obese women [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ballestri S et al showed ultrasonographic fatty liver indicator (US-FLI) can accurately identify the severity of histology and is also correlated with WC, BMI, and IR with various steatogenic liver diseases [34]. In addition, Nelson SM et al demonstrated that US-FLI may differentiate steatosis from NASH in the average obese population [35]. Praveenraj et al reported that BMI, WC and WHR had the best predictive ability for NAFLD in a cohort of morbidly obese women [36].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy of the ultrasound is also limited in patients with fibrosis, chronic liver dysfunction, high body mass index (BMI > 40 kg/m 2 ) or in the presence of ascites [ 141 , 142 , 143 ]. These limitations can be partially overcome with the use of semi-quantitative measures, such as the ultrasonographic fatty liver indicator (US-FLI score) [ 144 ]. The US-FLI uses sonographic metrics (hepato-renal contrast, posterior attenuation, blurring of portal veins and hepatic veins, limited visualisation of the gallbladder wall, limited visualisation of the diaphragm and areas of focal fatty sparing) to generate a score of mild, moderate and severe steatosis.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Studies demonstrate excellent inter-observer reproducibility and good differentiation of severity, with high specificity (90%) and sensitivity (90%) even in mild steatosis (>10% fatty infiltration) [ 145 , 146 ]. The US-FLI score has also been found to differentiate steatosis from NASH in the obese population, especially when the score is ≤4 with a negative predictive value of 88% and sensitivity of 91% for absence of NASH [ 144 ].…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Our study analyzed the retrospective ultrasonographic records describing by the original criteria which performed by Saverymuttu et al [ 13 ]. The criteria were widely accessed by general physicians, and our ultrasonographic findings were still valuable in differentiating from steatosis to nonalcoholic steatohepatitis (NASH) [ 45 , 46 , 47 ]. Our study design was limited by the initial health care setting to confidently exclude advanced fibrosis, but we still focused on the relationship between ultrasonographic finding and specific coronary calcification.…”
Section: Discussionmentioning
confidence: 99%